Molecular Basis of Encapsidation of Hepatitis C Virus Genome - Shi, Guoli; Suzuki, Tetsuro (Frontiers in Microbiology, 2018)
Hepatitis C virus (HCV), a major etiologic agent of human liver diseases, is a positive-sense single-stranded RNA virus and is classified in the Flaviviridae family. Although research findings for the assembly of HCV particles are accumulating due to development of HCV cell culture system, the mechanism(s) by which the HCV genome becomes encapsidated remains largely unclear. In general, viral RNA represents only a small fraction of the RNA molecules in the cells infected with RNA viruses, but the viral genomic RNA is considered to selectively packaged into virions. It was recently demonstrated that HCV RNAs containing 3’ end of the genome are selectively incorporated into virus particles during the assembly process and the 3’ untranslated region functions as a cis-acting element for RNA packaging. Here, we discuss the molecular basis of RNA encapsidation of HCV and classical flaviviruses, contrast with the packaging mechanism of HIV-1.